Social Work and Society: Pathways Towards a Global Public Sphere - Marie Frühauf; Fabian Kessl (Social Work and Society, 2024)
A succession of global crises defines the first two decades of the 21st century. Crises already dominated main parts of the 20th century - and are part of the modern societies in general. But the global dimension of the current crises, first and foremost the pandemic and the climate crisis, is unprecedented. In contrast, social security and social care programs and strategies are still anchored in and oriented towards the nation state. Therefore, they react with a corresponding uncertainty or simplified security promises only on the national level. Exceptions on a supranational level, such as attempts to strengthen the social dimension in the European Union (EU), are only partially successful. This is not least because the European unification was primarily motivated by the economic strengthening of the member states and the European economy in general. Aspects like social security as well as the democratic legitimacy of the EU always lagged behind. This seemed to be legitimate as long as a certain division of labour seemed to work: transnational cooperation strengthens economic dynamics and the necessary social integration is established at the national level. With the need to manage the current global crises and prevent their further escalation, the question of an actual global welfare policy and a global public sphere is moving to the centre of attention.